Agaricus brasiliensis Mushroom Protects Against Sepsis by Alleviating Oxidative and Inflammatory Response - Navegantes-Lima, Kely Campos; Monteiro, Valter Vinicius Silva; de França Gaspar, Silvia Leticia; de Brito Oliveira, Ana Ligia; de Oliveira, Juliana Pinheiro; Reis, Jordano Ferreira; de Souza Gomes, Rafaelli; Rodrigues, Caroline Azulay; Stutz, Herta; Sovrani, Vanessa; Peres, Alessandra; Romão, Pedro Roosevelt Torres; et al. (Frontiers in Immunology, 2020)
Sepsis is characterized by the host's dysregulated immune response to an infection followed by a potentially fatal organ dysfunction. Although the advances in sepsis treatment, mainly focused on broad-spectrum antibiotics, mortality rate of patients with septic shock remains high. Therefore it is important to investigate new therapies for treatment of this syndrome. Oxidative stress is one of the main features in septic patients, so antioxidants can be a good alternative for treatment. Agaricus brasiliensis is a nutraceutical rich in bioactive compounds such as polyphenols and polysaccharides, exhibiting antioxidant, antitumor and immunomodulatory activities. Here, we investigated the immunomodulatory and antioxidant effects of A. brasilensis aqueous extract in the cecal ligation and puncture (CLP) sepsis model. Our data showed that aqueous extract of A. brasiliensis improved survival and clinical parameters of septic mice, reduced systemic inflammation and oxidative inflammatory response, reduced leukocyte migration to the peritoneal cavity and increased phagocytosis, nitric oxide production and bacteria clearance. Moreover, A brasiliensis reduced the oxidative stress markers in all evaluated organs, as well as decreased the oxidative stress in vitro and DNA damage. In conclusion, the aqueous extract of A. brasiliensis have immunomodulatory and antioxidant capacity both in vitro and in vivo.